Dose-dependent enhancement of in vitro osteogenic activity on strontium-decorated polyetheretherketone - Yongheng Zhang; Lvhua Liu; Mengqi Li; Shufu Wang; Jingjing Fu; Mingyuan Yang; Chunxi Yan; Ying Liu; Yanyan Zheng (Scientific Reports)
Abstract Polyetheretherketone (PEEK) is widely used in orthopedic and dental implants due to its excellent mechanical properties, chemical stability, and biocompatibility. However, its inherently bioinert nature makes it present weak osteogenic activity, which greatly restricts its clinical adoption. Herein, strontium (Sr) is incorporated onto the surface of PEEK using mussel-inspired polydopamine coating to improve its osteogenic activity. X-ray photoelectron spectroscopy and ion release assay results confirm that different concentrations of Sr are incorporated onto the PEEK substrate surfaces. The strontium-modified PEEK samples show a stable Sr ion release in 35 days of detection. Better results of MC3T3-E1 pre-osteoblasts adhesion, spreading, and proliferation can be observed in strontium-modified PEEK groups, which demonstrates strontium-modified PEEK samples with the improved MC3T3-E1 pre-osteoblasts compatibility. The boosted osteogenic activity of strontium-modified PEEK samples has been demonstrated by the better performed of ALP activity, extracellular matrix mineralization, collagen secretion, and the remarkable up-regulation of ALP, OCN, OPN, Runx2, Col-I, BSP, and OSX of the MC3T3-E1 pre-osteoblasts. Additionally, the strontium-modified PEEK samples exhibit a dose-dependent enhancement of osteoblasts compatibility and osteogenic activity, and the PEEK-Sr10 group shows the best. These findings indicate that strontium-decorated PEEK implants show promising application in orthopedic and dental implants.